2006
DOI: 10.1177/003804070607900201
|View full text |Cite
|
Sign up to set email alerts
|

Coloring Outside the Lines: Racial Segregation in Public Schools and Their Attendance Boundaries

Abstract: Scholars have debated whether students' enrollment in private schools changes levels of racial segregation across urban school districts. The authors examine this issue by comparing the actual racial composition of schools with the racial composition of school-aged children living in the corresponding attendance areas. They do so by linking maps of school attendance boundaries with 2000 census data, the Common Core of Data, and the Private School Survey for the 22 largest U.S. school districts. The results sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
135
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(144 citation statements)
references
References 41 publications
7
135
0
2
Order By: Relevance
“…In Equation 1, the manner of defining an appropriate choice set plays a decisive role in explaining what features stimulate individual EMOs to get involved in a particular market, which is expected to allow the maximization of profits. Some studies establish potential choice sets within a given mile radius from homes (Bell, 2009;Burgess, Greaves, Vignoles, & Wilson, 2011;Cobb & Glass, 1999), and a number of scholars identify a charter school's catchment area as the Census geographic units and school attendance boundaries to which the charter school belongs (Garcia, 2008;Ritter, Jensen, Kisida, & Bowen, 2016;Saporito & Sohoni, 2006;Sohoni & Saporito, 2009). Even though these technical approaches may be a simple and convenient method, they have impeded the progress of research on access to charter schools with non-residence requirements in competitive markets.…”
Section: Market Density In Site Selectionmentioning
confidence: 99%
“…In Equation 1, the manner of defining an appropriate choice set plays a decisive role in explaining what features stimulate individual EMOs to get involved in a particular market, which is expected to allow the maximization of profits. Some studies establish potential choice sets within a given mile radius from homes (Bell, 2009;Burgess, Greaves, Vignoles, & Wilson, 2011;Cobb & Glass, 1999), and a number of scholars identify a charter school's catchment area as the Census geographic units and school attendance boundaries to which the charter school belongs (Garcia, 2008;Ritter, Jensen, Kisida, & Bowen, 2016;Saporito & Sohoni, 2006;Sohoni & Saporito, 2009). Even though these technical approaches may be a simple and convenient method, they have impeded the progress of research on access to charter schools with non-residence requirements in competitive markets.…”
Section: Market Density In Site Selectionmentioning
confidence: 99%
“…In Washington, DC, parents' preferences of charter schools were also more racially-based than their responses to a survey in which parents reported that school composition did not matter (Buckley & Schneider, 2007). Research in other contexts found that a school district's diversity was associated with higher enrollment by Whites into disproportionately White charter schools, a trend that did not seem to be significantly affected by a school's academic quality (Renzulli & Evans, 2005; see also Saporito & Sohoni, 2006 for school choice more generally). A study of upstate New York metropolitan areas-demographically similar in many respects to Pennsylvania-found that White parents' school choices were strongly influenced by wanting their children to attend a school with fewer non-Whites (Lankford & Wyckoff, 2005).…”
Section: Understanding School Choicesmentioning
confidence: 99%
“…Additional work has asked parents to rank factors that influenced their decisions to attend non-neighborhood schools including factors that have geographic components such as transportation, distance from home, and convenience (Blank, Levine, & Steel, 1996;David, West, & Ribbens, 1994;Gill, Timpane, Ross, & Brewer, 2001). Finally, a handful of researchers have used geographic tools to consider the degree to which choice has produced segregation and movement of students between districts (Cobb & Glass, 1999;Lubienski, 2005;Saporito & Sohoni, 2006). While the role of geography ranges from peripheral to central, taken together, these studies suggest geography matters in parents' decisions regarding schools.…”
Section: The Relationship Between Policy and Geographymentioning
confidence: 99%